Trends and Research Focus of Plant Awareness in Biology Learning: A Bibliometric Analysis - Zebua, Nofamataro; Zebua, Ester Novi Kurnia (Bioedusiana: Jurnal Pendidikan Biologi, 2025)
Plants are fundamental components of life and ecosystems, yet human awareness of their importance is low compared to that of animals-a phenomenon known as the plant awareness disparity. Therefore, mapping the direction and focus of research on plant awareness in learning is important to strengthen the scientific and pedagogical basis in facing sustainability challenges. This article aims to analyze the trends, main actors, thematic focus, and direction of plant awareness research development in the context of learning based on Google Scholar-indexed scientific publications for the period 2020-2025, using a bibliometric approach. A total of 62 articles were analyzed with the help of VOSviewer software to explore keyword patterns, collaboration networks, and the identification of the most productive institutions and authors. The analysis showed a significant increase in the number of publications, especially from 2022 to 2024, with the highest spike in 2023 (n=21 articles). The main contributors in this area were K.M. Parsley and B.C. Stagg, who each contributed two publications. The research focus is divided into several thematic clusters, such as student perceptions of plants, sustainable education, botanical visualization, and science curriculum integration. The findings confirm the importance of integrating awareness of growing.